Use of a point-of-care portable blood analyzer for evaluation of blood gas analytes and select physiologic parameters in the American flamingo (Phoenicopterus ruber). (January 2016) - Gardhouse, S.; Eshar, D.
Abstract This study was conducted in order to evaluate blood gas analytes using a portable clinical analyzer in captive American flamingos (Phoenicopterus ruber ). Seventeen healthy flamingos were evaluated as part of an overall clinical health assessment. Each bird underwent a complete physical examination, complete blood count, and serum biochemistry testing. Blood samples were collected from the medial metatarsal vein and using the VetScan i-STAT® analyzer, tested for the following parameters: hydrogen ion concentration, oxygen tension, carbon dioxide tension, sodium, potassium, ionized calcium, hematocrit, and various calculated parameters. The different parameters of venous blood gas were described using the mean, median, the interquartile range, P2.5 and P97.5, and minimum and maximum values. A comparison between sexes revealed no significant difference (p > 0.05) in any of the observed values. The test provided rapid results and was easy to use, making it useful for point-of-care use in zoological settings, or hospitalized critical avian patients. Knowledge of baseline parameters can promote better physiological understanding and improve clinical management of this avian species.